ASSERTIVE ILLOCUTIONARY ACT USED BY PRESIDENT JOE BIDEN IN HIS SELECTED SPEECHES - Ni Wayan Kesuma Dewi; Ida Ayu Putri Gita Ardiantari (Lire Journal (Journal of Linguistics and Literature), 2026)
This study examines assertive illocutionary acts in President Joe Biden’s political speech using Searle’s (1979) speech act theory as the analytical framework. In political discourse, language functions not only to convey information but also to perform actions such as stating beliefs, presenting claims, and shaping audience understanding. This research focuses on how assertive speech acts are used to express viewpoints, organize ideas, and construct political messages. The data were taken from President Joe Biden’s Farewell Address to the Nation and analyzed using a descriptive qualitative method. A total of 24 assertive utterances were identified and classified into five types: asserting, concluding, describing, claiming, and reporting. Asserting is the most dominant type with 8 occurrences (33.4%), followed by describing and claiming with 5 occurrences each (20.8%). Concluding and reporting each appear 3 times (12.5%). The findings indicate that assertive illocutionary acts are frequently used to present beliefs, explain situations, and evaluate political actions. This study contributes to pragmatic analysis by showing how assertive acts function within an authentic political speech and how they support political communication through structured and purposeful language use.